Diagnosis and Antibiotic Management of Otitis Media and Otitis Externa in United States Veterans. (4th October 2019) - Pontefract, Benjamin; Nevers, Mckenna; Fleming-Dutra, Katherine E; Hersh, Adam; Samore, Matthew; Madaras-Kelly, Karl
Abstract: Background: Acute otitis media (AOM) and otitis media with effusion (OME) occur primarily in children, whereas acute otitis externa (AOE) occurs with similar frequency in children and adults. Data on the incidence and management of otitis in adults are limited. This study characterizes the incidence, antibiotic management, and outcomes for adults with otitis diagnoses. Methods: A retrospective cohort of ambulatory adult veterans who presented with acute respiratory tract infection (ARI) diagnoses at 6 VA Medical Centers during 2014–2018 was created. Then, a subcohort of patients with acute otitis diagnoses was developed. Patient visits were categorized with administrative diagnostic codes for ARI (eg, sinusitis, pharyngitis) and otitis (OME, AOM, and AOE). Incidence rates for each diagnosis were calculated. Proportions of otitis visits with antibiotic prescribing, complications, and specialty referral were summarized. Results: Of 46 634 ARI visits, 3898 (8%) included an otitis diagnosis: OME (22%), AOM (44%), AOE (31%), and multiple otitis diagnoses (3%). Incidence rates were otitis media 4.0 (95% confidence interval [CI], 3.9–4.2) and AOE 2.0 (95% CI, 1.9–2.1) diagnoses per 1000 patient-years. By comparison, the incidence rates for pharyngitis (8.4; 95% CI, 8.2–8.6) and sinusitis (15.2; 95% CI, 14.9–15.5) were higher. Systemic antibiotics were prescribed in 75%, 63%, and 21% of AOM, OME, and AOE visits, respectively. Complications for otitis visits were low irrespective of antibiotic treatment. Conclusions: Administrative data indicated that otitis media diagnoses in adults were half as common as acute pharyngitis, and the majority received antibiotic treatment, which may be inappropriate. Prospective studies verifying diagnostic accuracy and antibiotic appropriateness are warranted.